COMPARISON OF AIRFLOW IN TYPE 36 LOW-INCOME HOUSING UNIT USING CFD SIMULATION - lestari, lestari; Muazir, Syaiful (DIMENSI (Journal of Architecture and Built Environment), 2021)
Type 36 houses are built for people who have low income. Because of this, the buildings’ ventilation relies on natural airflow. One of the variables that affects natural ventilation is airflow. Airflow can affect the quality of indoor air, influencing the comfort and health of those within. This study aims to evaluate the designs of type 36 buildings from the perspective of the airflow through the unit. It uses computational fluid dynamics simulations to compare the pattern and velocity of airflow in each building design. There are six designs of type 36 house that have different layouts and placements of air vents. The results of the simulation and analysis show that rooms arranged in a way that allows for the placement of vents that were facing each other, even if they were in different rooms, generated continuous airflow without experiencing turbulence.